Performance analysis of broadband CDMA communication system - Cheng, Xun. (2010)
A Broadband CDMA (B-CDMA) communication system, which can provide integrated services (video-conferencing, voice and data), is proposed to meet the demand of the Personal Communication System (PCS). In this system, video-conferencing/voice services are given a higher priority as compared to data services since they need real-time delivery. Data traffic has a lower priority due to its tolerance to delay. A new channel structure and some call admission control schemes are also developed. The performance of the proposed admission control schemes is investigated and some results from the theoretical analysis are validated by computer simulations.